2021
DOI: 10.36849/jdd.5657
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Hedgehog Inhibitors Sonidegib and Vismodegib for Treatment of Advanced Basal Cell Carcinoma

Abstract: Basal cell carcinoma (BCC) is the most common malignancy in fair-skinned populations. Most cases are successfully treated with surgery, but in advanced BCC-including locally advanced BCC and metastatic BCC-surgery is likely to result in substantial morbidity or unlikely to be effective. In those patients, the systemic Hedgehog inhibitors (HHIs) sonidegib and vismodegib are the only approved pharmacologic treatment option. Although a number of clinical studies highlight the similarities and differences between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 38 publications
1
23
0
5
Order By: Relevance
“…The approved dose is 150 mg once a day [ 90 ]. Approval was based on the ERIVANCE study which showed remission rates of 49 % for mBCC and 60 % for laBCC after 39 months of follow‐up, with a median duration of response of 15 months (mBCC) and 26 months (laBCC) [ 91 , 92 ]. The results of the ERIVANCE study have been confirmed in another international multicenter study (STEVIE), with response rates of 69 % for laBCC and 37 % for mBCC, with an average duration of response of 23, and 14 months, respectively [ 92 , 93 ].…”
Section: Treatmentmentioning
confidence: 99%
“…The approved dose is 150 mg once a day [ 90 ]. Approval was based on the ERIVANCE study which showed remission rates of 49 % for mBCC and 60 % for laBCC after 39 months of follow‐up, with a median duration of response of 15 months (mBCC) and 26 months (laBCC) [ 91 , 92 ]. The results of the ERIVANCE study have been confirmed in another international multicenter study (STEVIE), with response rates of 69 % for laBCC and 37 % for mBCC, with an average duration of response of 23, and 14 months, respectively [ 92 , 93 ].…”
Section: Treatmentmentioning
confidence: 99%
“…Vismodegib war der erste verfügbare HHI und ist für die Therapie des mBZK und auch des lfBZK zugelassen, wenn eine Operation oder Strahlentherapie nicht in Frage kommen. Patienten mit BZK-Syndrom, die multiple BZK aufweisen, stellen auch eine Therapieindikation für HHI dar Direkte Vergleichsstudien zwischen den beiden Medikamenten gibt es nicht und in den Zulassungsstudien wurden unterschiedliche Designs verwendet [87,92]. Die Effektivität von Sonidegib und Vismodegib beim lfBZK sowie ihr Nebenwirkungsprofil werden aber als ähnlich erachtet [87].…”
Section: Hedgehog-inhibitorenunclassified
“…Die zugelassene Dosis beträgt 150 mg 1 x täglich [90]. Die Zulassung basiert auf der ERIVANCE‐Studie, die im Langzeit‐Follow‐up nach 39 Monaten eine Remissionsrate von 49 % für das mBZK und von 60 % für das lfBZK bei einer medianen Ansprechdauer von 15 beziehungsweise 26 Monaten zeigte [91, 92]. Die Resultate der ERIVANCE‐Studie wurden in einer weiteren internationalen Multicenterstudie (STEVIE) bestätigt, mit Ansprechraten von 69 % für das lfBZK und 37 % für das mBZK bei einer mittleren Ansprechdauer von 23 beziehungsweise 14 Monaten [92, 93].…”
Section: Therapieunclassified
See 2 more Smart Citations